Compulsive internet use, religious beliefs, and family sex communication as predictors of sexual shaming among Malaysian young adults - Kong, Chin Mun; Kong, Wei Leng; Thong, Kai Lim (2024)
Sexual shaming is a multifaceted issue influenced by various personal and societal factors, including religiosity, familial communications, and digital media consumption. The study examines the predictive effects of compulsive internet use for sexually explicit media, religious beliefs, and family sex communication on sexual shame among Malaysian young adults. A cross-sectional quantitative design was employed using convenience and purposive sampling. The final sample consisted of 278 participants (Mage = 23.45; SDage = 2.93), with 63.3% females. In terms of ethnicity, the majority were Chinese (84.2%), followed by Malays (7.2%), Indians (6.5%), and other ethnicities (2.2%). The data were obtained by the Compulsive Internet Use Scale for Sexually Explicit Media (CIUS-SEM), Centrality of Religiosity Scale (CRS), Family Sex Communication Quotient (FSCQ), and Revised Sexual Shame Inventory (SSI-R). The results of the multiple linear regression analysis indicated that compulsive internet use was a significant positive predictor of sexual shame (β = .233, p < .001), while religious beliefs (β = -.069, p = .249) and family sex communication (β = .065, p = .272) were not significant predictors. The findings suggest that prolonged exposure to sexually explicit media increased vulnerability to sexual shame. Meanwhile, the lack of predictive effects for religious beliefs and family sex communication may reflect the cultural and demographic influences, such as the prevalence of Buddhism in the sample. The study not only illuminates new perspectives into sexual shame within the diverse multiracial and multireligious framework of Malaysian society but also highlights the need for context-specific interventions and policies to address the complex interplay of personal, cultural, and societal factors that shape sexual attitudes and behaviours.